Pengaruh Additif Xanthan Gum Terhadap Sifat Rheology Fluida Pemboran - Abdullah Rizky Agusman; Edy Soesanto; Mohamad Rizqi Putra Prasetyo (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
Drilling mud is a critical fluid in the drilling process, serving to maintain wellbore stability, transport drill cuttings, cool and lubricate the drill bit, and control formation pressure. In this study, a formulation was developed using bentonite, barite, and xanthan gum in specific proportions: 22.5 grams of bentonite, 11 grams of barite, and 8-11 grams of xanthan gum. The objective was to optimize the mud properties for a particular formation. After preparation, the mud was subjected to a series of tests in accordance with API standards, including density, rheological properties, filtration loss, and mud cake formation. The results demonstrated that the mud met the API criteria, with a density range of 9-9.5 ppg, a plastic viscosity (PV) between 13-20 cp, a yield point (YP) between 20-25 lb/100ft², 10-second gel strength between 14-21 lb/100ft², 10-minute gel strength between 17-24 lb/100ft², filtration loss between 9-14.7 ml, and mud cake thickness ranging from 1.47-1.76 mm. These findings indicate that the formulated drilling mud is capable of effectively stabilizing the wellbore, lifting drill cuttings, and minimizing the risks of kicks and lost circulation, thereby enhancing the overall efficiency and safety of the drilling operation in the targeted formation.